Efektivitas Peran Resort Konservasi Wilayah Meulaboh Dalam Perlindungan Terhadap Penyu Sebagai Satwa Yang Dilindungi - Ulfa Indriani; Putri Keumala Sari (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Sea turtles are one of the protected animals, protection for sea turtles is regulated in Law Number 5 of 1990 concerning Conservation of Biological Natural Resources and their Ecosystems. However, lately trade and hunting for eggs to be traded has been rife, one of which is in the Meulaboh area. This poses a serious threat to turtle populations. In Meulaboh the institution that plays a role in protecting sea turtles is the Meulaboh Regional Conservation Resort. This study aims to find out how effective the role of the Meulaboh Region Conservation Resort is in protecting sea turtles as a protected animal and what obstacles are faced. This study uses empirical juridical research methods, namely direct research into the field. Data collection was carried out using interview techniques with the Conservation Resort in the Meulaboh area and Hunters and Turtle Egg Traders around the Meulaboh area, as well as collecting data by means of a literature study. The results of the study show that illegal hunting and trading of turtle eggs is still rife in the Meulaboh area. The effectiveness of the role of the Natural Resource Conservation Resort in the protection and preservation of sea turtles has not been effective. Supervision and efforts made by the Resort are still not optimal. The lack of optimal supervision and protection of sea turtles carried out by the Meulaboh Regional Conservation Resort is caused by several obstacles, namely, a lack of personnel, lack of infrastructure and lack of operational vehicle facilities which prevent officers from getting to the location and the existence of overlapping government policies.